Plant Defense and Antimicrobial Peptides - Castro, M.S.; Fontes, W.
Plants are constantly exposed to a large array of pathogenic organisms and the survival in these conditions demands quick defense responses which include the synthesis of defense peptides and proteins with antimicrobial properties. The main groups of antimicrobial peptides found in plants are thionins, defensins and lipid transfer proteins. They constitute interesting candidates to engineer disease resistance in plants.
Keywords: PLANT DEFENSE; ANTIMICROBIAL PEPTIDES; THIONINS; DEFENSINS; LIPID TRANSFER PROTEINS